DNA Damage Sensor γ-H2AX Is Increased in Preneoplastic Lesions of Hepatocellular Carcinoma. (3rd March 2013) - Matsuda, Yasunobu; Wakai, Toshifumi; Kubota, Masayuki; Osawa, Mami; Takamura, Masaaki; Yamagiwa, Satoshi; Aoyagi, Yutaka; Sanpei, Ayumi; Fujimaki, Shun
Abstract : Background . Phosphorylated histone H2AX ( γ -H2AX) is a potential regulator of DNA repair and is a useful tool for detecting DNA damage. To evaluate the clinical usefulness of γ -H2AX in hepatocellular carcinoma (HCC), we measured the level of γ -H2AX in HCC, dysplastic nodule, and nontumorous liver diseases. Methods . The level of γ -H2AX was measured by immunohistochemistry in fifty-eight HCC, 18 chronic hepatitis, 22 liver cirrhosis, and 19 dysplastic nodules. Appropriate cases were also examined by fluorescence analysis and western blotting. Results . All cases with chronic liver disease showed increased levels of γ -H2AX expression. In 40 (69.9%) of 58 cases with HCC, the labeling index (LI) of γ -H2AX was above 50% and was inversely correlated with the histological grade. Mean γ -H2AX LI was the highest in dysplastic nodule ( 74.1 ± 22.1 % ), which was significantly higher than HCC ( P < 0.005 ) . Moreover, γ -H2AX was significantly increased in nontumorous tissues of HCC as compared with liver cirrhosis without HCC (62.5 ± 24.7 %, from 5.1 to 96.0%, P < 0.005 ). Conclusions . γ -H2AX was increased in the preneoplastic lesions of HCC and might be a useful biomarker for predicting the risk of HCC.